2009
DOI: 10.1242/dmm.003251
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and failure of pancreatic β cells in murine models with different degrees of metabolic syndrome

Abstract: SUMMARYThe events that contribute to the expansion of -cell mass and enhanced -cell function in insulin-resistant states have not been elucidated fully. Recently, we showed that -cell adaptation failed dramatically in adult, insulin-resistant POKO mice, which contrasts with the appropriate expansion of  cells in their ob/ob littermates. Thus, we hypothesised that characterisation of the islets in these mouse models at an early age should provide a unique opportunity to: (1) identify mechanisms involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Consistent with these observations, we demonstrated that ghrelin reduces the hypothalamic levels of CHOP-10 and the phosphorylated form of its upstream regulator phosphorylated eukaryotic translation initiation factor 2a (peIF2a; Lage et al 2010). Taking into account that 1) hypothalamic ER stress has recently been suggested as a pathophysiological mechanism mediating leptin resistance and obesity (Hosoi et al 2008, Zhang et al 2008, Ozcan et al 2009, Martínez de Morentin et al 2010b, de Morentin & López 2010, Ropelle et al 2010 and 2) central ghrelin administration increases hypothalamic reactive oxygen species (ROS; Andrews et al 2008), which are well-recognized ER-stress inducers , Tagawa et al 2008, Medina-Gomez et al 2009, Santos et al 2009, Martínez de Morentin et al 2010b, we have recently proposed that ghrelin-induced elevation in hypothalamic pFOXO1 might be part of an allostatic response protecting against ER stress ), a hypothesis that will involve further investigation.…”
Section: Ghs-r 1asupporting
confidence: 72%
“…Consistent with these observations, we demonstrated that ghrelin reduces the hypothalamic levels of CHOP-10 and the phosphorylated form of its upstream regulator phosphorylated eukaryotic translation initiation factor 2a (peIF2a; Lage et al 2010). Taking into account that 1) hypothalamic ER stress has recently been suggested as a pathophysiological mechanism mediating leptin resistance and obesity (Hosoi et al 2008, Zhang et al 2008, Ozcan et al 2009, Martínez de Morentin et al 2010b, de Morentin & López 2010, Ropelle et al 2010 and 2) central ghrelin administration increases hypothalamic reactive oxygen species (ROS; Andrews et al 2008), which are well-recognized ER-stress inducers , Tagawa et al 2008, Medina-Gomez et al 2009, Santos et al 2009, Martínez de Morentin et al 2010b, we have recently proposed that ghrelin-induced elevation in hypothalamic pFOXO1 might be part of an allostatic response protecting against ER stress ), a hypothesis that will involve further investigation.…”
Section: Ghs-r 1asupporting
confidence: 72%
“…In contrast, mice with islet specific knockout of PPARγ did not become hyperglycemic [81], indicating that the POKO mouse phenotype is not due to loss of PPARγ in islets. Lipidomic analysis of islets isolated from POKO and PPARγ2 KO mice at 4 weeks of age showed no dysregulation of lipid content [82], whereas at 16 weeks diacylglycerides and short chain tri-acylglycerides were decreased in the knockout strains compared to wild-type. This was associated with decreased levels of ethanol-amine plasmalogen (36:2), and increased levels of phosphatidylethanolamine (36:2) and ceramides (20:0 and 22:0) in islets of POKO mice compared to PPARγ2 knockouts -and wild type mice [80].…”
Section: β-Cell Dysfunction and T2dmentioning
confidence: 99%
“…We previously generated a mouse model of PPARγ2 deficiency (PPγ2KO) (11), which is insulin resistant and presents adipose tissue dysfunction, particularly when challenged with positive energy balance (12). Moreover, PPARγ2 seems to be important for pancreatic β-cell mass adaptation in murine models of the metabolic syndrome (13,14). We previously showed that PPARγ agonists reverse IR associated with late pregnancy in rats (3), and there is evidence that PPARg expression in adipose tissue in obese women with GDM is lower than in obese women with an uncomplicated pregnancy (15).…”
Section: Insulin Stimulationmentioning
confidence: 99%